Blackness in Israel : rethinking racial boundaries - Dorchin, Uri; Djerrahian, Gabriella (Abingdon, Oxon ; New York, NY : Routledge, 2021)
Allowing a new perspective on the sociology of Israel and the realm of black studies, this volume reveals a highly nuanced portrait of the phenomenon of blackness, one that is located at the nexus of global, regional, national and local dimensions. While race has been discussed as it pertains to Judaism at large, and Israeli society in particular, blackness as a conceptual tool divorced from phenotype, skin tone and even music has yet to be explored. Grounded in ethnographic research, the study demonstrates that many ethno-racial groups that constitute Israeli society intimately engage with blackness as it is repeatedly and explicitly addressed by a wide array of social actors.
Background Predicaments of Jewishness and blackness -- The image of the black in Jewish culture An overview -- Jewishness, blackness and genetic data Israeli geneticists and physicians tracing the ancestry of two African populations -- Blackness in the Jewish Israeli society Race and Ethiopian Jewish blackness in Israel An ethnographyh -- Black-Israeli lives matter Online activism among young Ethiopian Israelis -- Blackness in translation The Israeli Black Panthers, 1971 -- Blackness, Mizrahi identity and ethnic shifting in contemporary Israeli popular music -- A different hue of blackness The Haredi case -- Contested blackness -- "I am blacker than you" Mizrahiness and Ethiopianess in an educational boarding school in Israel -- Black city Sounding race, territory and belonging in Tel Aviv's "African refugee crisis" -- Trajectories of soul citizenship African dance clubs between global blackness and local awareness -- Already black ... and proud, and righteous The African Hebrew Israelite Community in the State of Israel -- Blackness and the Israeli-Palestinian conflict -- What is the color of the Arab? A critical view of color games -- What color are Israeli Jews?
OCLC-licensed vendor bibliographic record.
Keywords: Blacks -- Israel; Israel -- Race relations; SOCIAL SCIENCE / Ethnic Studies / General; HISTORY / Middle East / Israel